Representasi Perempuan Cantik di Media Feminis Daring Jurnal Perempuan dan Magdalene - Meylisa Yuliastuti Sahan; Denik Iswardani Witarti (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2021)
Women in their efforts to end the subordination of their bodies and create a body positivity movement then formed their own media with a feminist perspective such as Jurnal Perempuan and Magdalene. This study aims to analyze and explain the form of representation of beautiful women in the feminist media of Jurnal Perempuan and Magdalene using Sara Mills' critical discourse analysis theory with a feminist perspective that looks at the text from the subject-object and writer-reader side and its relationship to the circumstances when the text was produced. The results of this study explain that women must find a way out to believe the existing beauty myths. the definitions of beautiful women and beauty from the Journal of Women and Magdalene do not differ much, these two media try to explain and convince that there has never been a right definition to explain women's beauty itself, the definition and shape of the boxes on women's beauty are wrong. and the pursuit of beauty is not right. Beautiful women must be interpreted more broadly than just physical appearance.